Gambaran dan Faktor-faktor Schadenfreude pada Politisi: Studi Fenomenologi - Rachmadani, Dinda Putri; Suyono, Hadi (Universitas Islam Indonesia, 2023)
The era of post-truth has caused many cases where politicians bring down their opponents in various ways to get pleasure. This pleasure is known as schadenfreude. This study aims to determine the description and factors that influence scadenfreude in politicians. The subjects in this study were regional-level politicians from one of the Z political parties in city X as many as three subjects. The research method used in this research is a qualitative research method with a phenomenological approach. The main data collection technique in this study used semi-structured interviews. The data analysis technique in this study used content analysis. Researchers used triangulation of data sources with significant persons to meet the data validity requirements. The findings show that there is schadenfreude in politicians. Schadenfreude's emotional appears to politicians because of competition and tend to favor their own party. Politicians expect their opponents to lose, so they are happy with their victory. The defeat received by an opponent with bad morals is deemed appropriate to feel happy if the opponent loses. This research is an illustration for politicians not to engage in behavior related to schadenfreude because it has a negative impact on the democratic process.